MODEL ELABORATION LIKELIHOOD DALAM PEMBENTUKAN PERSONAL BRANDING PITAâ€™S LIFE DI YOUTUBE CHANNEL - Sahertian, Christiana; Kue, Maria Fatima (Jurnal Nomosleca, 2019)
Abstrack This study aims to describe the formation of the personal pranding Pita 's Life vlog on youtube through the analysis of Model Elaboration Likelihood. From this research, it is expected to provide input and advice to the Youtuber to better display content that is better and not detrimental to themselves and others, so as to produce a positive outlook on their personal. The type of research used in this research is qualitative descriptive using the content analysis design. The use of the content analysis method was carried out in this study because the source of the data produced was verbal communication from the vlog of the Ribbon which was then re-identified in writing. The population used in this study was 64 'Pita's Life vlog shows from July to November 2018. The sample used in this study was the Pita Vlog show which only aired a life of 20 husbands and children. This research proves that the formation of the Pita 's Life vlog personal branding on Youtube can be analyzed using the Model Elabation Likelihood. This is because both the central line and peripheral lines in the Elaboration Likelihood Model are both processes in forming the Ribbon personal branding. In the central path, it shows that the arguments uttered by the Pita contain positive things. The argument expressed by Pita is also supported by its quality as a source of messages that appears to have ethos, attractions and power on peripheral lines, so both the argumentation and quality of the Ribbon as a communicator make Pita's vlog show an interesting show to be watched by the public. Keyword : Elaboration Likelihood Model, Personal Branding, Youtube ChannelDOI :Â https://doi.org/10.26905/nomosleca.v5i1.2985